MISTERI NAFS AL-WAHIDAH DALAM ALQUR’AN - Jumni Nelli (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2010)
This paper discusses the creation of woman in the Quran that can be identified by clear principles of the Quran about woman. In the Quran it is not found the verses in detail to tell the origins of woman's events. The only paragraph that suggests the origin of the woman's event is Surat an-Nisa (4:1) . The mufassirs still have different opinion, who exactly is meant by